Democracy of Breath and Fire: Irigarayan Meditations - Škof, Lenart (Sophia, 2022)
In this article, we are arguing for a possibility of a new elemental politics as based on breath and fire and gesturing beyond the modes and principles of ontology of violence, power struggles and war in philosophy and political philosophy. We first discuss the task of today’s political philosophy as a need to enkindle the humanity towards a new alliance in creativity and belonging. We propose a new, elemental approach, based on the revitalization of air/breath and fire and present Luce Irigaray’s thought as a key intervention of this kind within the contemporary political thought. The second part brings an analysis of texts by Ernst Jünger and Alain Badiou on soldiers and war as examples of an unfortunate philosophical adventure. The third part is our proposal for another genealogy of human beings as breathers and igniters within the new peaceful and mindful culture of democracy, providing us with a possibility of a new ethico-political order, as based on the elemental constellations of silence, breath and fire. Finally, the idea of a quiet democracy is established, as a place of inner horizontal calm being gathered and cultivated in us by fire, and as a place for beings of this Earth to breathe and to share the air within a new elemental-spiritual conspiracy of love. Towards the conclusion, this essay also is a hommage to Luce Irigaray’s approaches to ancient Indian religious and philosophical thinking.